Structure and properties of donor doped barium titanate prepared by citrate process - Stojanovic, B. D. [UNESP]; Zaghete, M. A. [UNESP]; Foschini, C. R. [UNESP]; Vieira, F. O S [UNESP]; Varela, José Arana [UNESP] (Taylor & Francis, 2002)
Niobium doped barium titanate was prepared using two procedures. First, doped barium titanate was prepared starting from citrate solutions of all components and second, pure barium titanate powder was obtained from the citrate solutions and after that doped. Besides niobium, a small amount of manganese, as acceptor dopant was added. Phase composition, crystal structure, microstructure and dielectric properties were reported. The influence of powder processing on the properties of niobium doped barium titanate was analysed. The grain growth and the concentration of dopants on the dielectric properties were considered. © 2002 Taylor & Francis.
Keywords: Dielectric properties; Doped barium titanate; Microstructure; Polymeric precursors; Crystal structure; Doping (additives); Grain growth; Niobium; Phase composition; Citrate process; Citrate solutions; Dopants; Barium titanate